Trichilemmal carcinoma treated by excision combined with photodynamic therapy: a case report and review of literature - Qidiao, Lingyu; Liu, Yilin; Hu, Danni; Tao, Xingchi; Yao, Chunli (Frontiers in Oncology, 2024)
Trichilemmal carcinoma is an extremely rare malignant cutaneous tumor derived from the outer root sheath of the hair follicles, which most commonly occurs in the sun-exposed areas of elderly individuals. This article introduces a case of trichilemmal carcinoma that occurred on the scalp of a 36-year-old male patient, the first case reported and treated with surgical excision combined with photodynamic therapy.